Pengembangan Konsep Landasan Robot Beroda Omnidirection Pemindah Barang Berbahan Extrusi Profil Aluminium - Ramdan, Ade; Prayoga, Reka Ardi; Ramadhan, Nur Jamiludin; Subekti, Irham; Anjani, Rifania (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2024)
This research examines how concept development was carried out to design an omnidirectional wheeled robot base made from extruded aluminum profiles used for moving goods. Concept design goes through a series of stages, that is: identifying problems, determining the function structure, looking for alternative solutions, building concept variations, assessing concept variations and determining the selected concept. After going through all these stages, it was concluded that an omnidirectional robot base can be divided into 2 sub-functions, namely: base frame and electrical energy converter. These two sub-functions have 6 parameters that can be varied, such as: various frame shapes, type of frame material, type of frame bar shape, type of frame connection, type of wheel, type of motor. Alternative solutions can be sought for each parameter, combined and assessed to obtain a variation of the selected concept that meets the list of requirements.